Effect of feeding rate on growth and feed conversion ratio in the cultivation recirculation systems of multi tropic model. Issue 1 (1st December 2022) - Heriansah,; Syamsuddin, R; Najamuddin,; Syafiuddin,
Abstract: The effects of feeding rate (0.5%, 7.5%, and 10% body weight [BW] per day [BW day −1 ]) on the growth, survival rate, and feed conversion ratio of rabbit fish, Siganus guttatus, (initial BW of 2.0 ± 0.5 g, density of 16 individuals 80 L −1 ) were investigated in a water recirculating aquaculture system of Integrated Multi Trophic Aquaculture (IMTA model involving mussel Perna viridis, sea urchin Diadema sitosum, and seaweed Kappaphycus alvarezii . Triplicate groups of fish were fed an comercial diet (55.4% protein, 14.1% lipid) four meals a day (8 a.m, 12 a.m, 4 p.m, dan 8 p.m) for 12 weeks. Survival rate (SR), body weight gain (BWG, specific growth rate (SGR), and feed conversion ratio (FCR) significantly affected (p<0.05) by feeding rate. Experimental application of the IMTA model shows that although the amount of feed given is higher, it can produce better growth performance.